2020
DOI: 10.1177/1535370220903270
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in uncovering non-invasive biomarkers of endometriosis

Abstract: Endometriosis affects up to 10% of women of childbearing age, causing symptoms that can include chronic pelvic pain and reduced fertility. The symptoms are not specific to the disease and can be confused with other gynecological conditions or normal menstruation. Currently, the disease can be only definitively diagnosed by laparoscopy, as no clinically accepted biomarker exists. Biomarker discovery can either follow a hypothesis-driven approach selecting targets to be tested based on current knowledge of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 75 publications
4
11
0
Order By: Relevance
“…Binding BDNF to TrKB, or activating PI3K pathway can inhibit proapoptotic protein activation and activate antiapoptotic protein Bcl-2 (9); or activating MAPK signaling pathway can in uence transcription factor and activate Bcl-2 (10); co-inhibit shedding endometrium from anoikis. Our study found that there was a signi cant difference in the expression of BDNF and TrKB between endometriosis endometrium and non-endometriosis endometrium, which is consistent with literature reported (11,12). Moreover, this study showed that the expression of BDNF and TrKB in ovarian endometriotic lesions was higher than that in eutopic endometrium, which is similar to Borghese et al found that the expression of BDNF in ovarian endometriotic lesions was higher than that in eutopic endometrium.…”
Section: Discussionsupporting
confidence: 92%
“…Binding BDNF to TrKB, or activating PI3K pathway can inhibit proapoptotic protein activation and activate antiapoptotic protein Bcl-2 (9); or activating MAPK signaling pathway can in uence transcription factor and activate Bcl-2 (10); co-inhibit shedding endometrium from anoikis. Our study found that there was a signi cant difference in the expression of BDNF and TrKB between endometriosis endometrium and non-endometriosis endometrium, which is consistent with literature reported (11,12). Moreover, this study showed that the expression of BDNF and TrKB in ovarian endometriotic lesions was higher than that in eutopic endometrium, which is similar to Borghese et al found that the expression of BDNF in ovarian endometriotic lesions was higher than that in eutopic endometrium.…”
Section: Discussionsupporting
confidence: 92%
“…Binding BDNF to TrKB, or activating PI3K pathway can inhibit proapoptotic protein activation and activate antiapoptotic protein Bcl-2 (9); or activating MAPK signaling pathway can in uence transcription factor and activate Bcl-2 (10); co-inhibit shedding endometrium from anoikis. Our study found that there was a signi cant difference in the expression of BDNF and TrKB between endometriosis endometrium and non-endometriosis endometrium, which is consistent with literature reported (11,12). Moreover, this study showed that the expression of BDNF and TrKB in ovarian endometriotic lesions was higher than that in eutopic endometrium, which is similar to Borghese et al who found that the expression of BDNF in ovarian endometriotic lesions was higher than that in eutopic endometrium.…”
Section: Discussionsupporting
confidence: 92%
“…Hudson showed that a specific plasma miRNA signature is associated with endometriosis, with miR-154-5p alone, or in combination with miR-196b, miR-378-3p, and miR-33a-5p. With this study, the total number of studies that evaluate the potential of circulating miRNAs as a diagnosis for endometriosis is 15 [ 69 ].…”
Section: The Role Of Circulating Mirnas In Endometriosismentioning
confidence: 99%